2019
DOI: 10.1002/adom.201901203
|View full text |Cite
|
Sign up to set email alerts
|

Lithography‐Free Random Bismuth Nanostructures for Full Solar Spectrum Harvesting and Mid‐Infrared Sensing

Abstract: A lithography‐free, double‐functional single bismuth (Bi) metal nanostructure is designed, fabricated, and characterized for ultrabroadband absorption in the visible (vis) and near‐infrared (NIR) ranges, and for a narrowband response with ultrahigh refractive index sensitivity in the mid‐infrared (MIR) range. To achieve a large‐scale fabrication of the design in a lithography‐free route, the oblique‐angle deposition approach is used to obtain densely packed and randomly spaced/oriented Bi nanostructures. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Yet, those sub-wavelength patterns demand lithographic fabrication, which are costly and cumbersome, especially for the applications of large surface areas and high working frequencies (i.e., tiny feature sizes). Therefore, the fabrication of PAs without the use of EB lithography, such as multilayer deposition 23 – 31 , oblique-angle deposition 32 , 33 , and chemical processes 34 36 , has been proposed to overcome the drawbacks of structural metamaterials. Among those methods, the multilayer deposition method outperforms others because the multilayer deposition method is not only more feasible, but also achieves the larger bandwidth and higher incident angle tolerance simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, those sub-wavelength patterns demand lithographic fabrication, which are costly and cumbersome, especially for the applications of large surface areas and high working frequencies (i.e., tiny feature sizes). Therefore, the fabrication of PAs without the use of EB lithography, such as multilayer deposition 23 – 31 , oblique-angle deposition 32 , 33 , and chemical processes 34 36 , has been proposed to overcome the drawbacks of structural metamaterials. Among those methods, the multilayer deposition method outperforms others because the multilayer deposition method is not only more feasible, but also achieves the larger bandwidth and higher incident angle tolerance simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the simultaneous formation of small and large particles could excite both FP and LSPR modes to achieve both semiconductor light absorption enhancement and plasmonic hot electron injection. In recent studies, we developed a facial route based on oblique angle deposition to synthesize plasmonic nanostructures on a large scale. Moreover, we demonstrated that as a result of the cyanide chemistry, so‐called CoFe‐Prussian blue analog (PBA) is a strong and robust water oxidation catalyst (WOC), when connected to an organic chromophore .…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the mechanistic factor controlling the nanostructural evolution of the films is an atomic scale "shadowing effect," which prevents the deposition of particles in regions situated behind initially formed nuclei (i.e., shadowed regions). We have successfully adopted this approach for the design of 3D ultra-broadband absorbers in visible, near-infrared (NIR) [53][54][55] and mid-infrared (MIR) [56,57] light-harvesting devices. Taking all into consideration, the oblique angle deposition, with its random geometry and capability to synthesize nanostructures with no material restriction, is an excellent approach to realize high-performance perfect absorbers in large-scale dimensions.…”
Section: Introductionmentioning
confidence: 99%